Analysis of palatability of cooked rice processed by high pressure treatment: A study of the using of high pressure treatment for cooking system in food service facilities - Akita, Seiko; Kakui, Miho; Asami, Yuya (Journal for the Integrated Study of Dietary Habits, 2025)
In Japan, food service facilities are introducing new cooking systems to improve operational efficiency and resolve labor shortages, but cost control remains an issue.In this study, with the aim of utilizing high pressure processing in a new cooking system for food service facilities, conducted to analyze palatability of cooked rice processed by high pressure treatment using both objective and subjective evaluation methods. In mechanical analysis of high pressure processed cooked rice, there was no significant difference in breaking characteristics between samples. The mechanical analysis confirmed that high-pressure treatment did not affect mechanical properties of cooked rice. On the other hand, changes in the color characteristics of the cooked rice were observed owing to the high pressure treatment. The moisture content of high pressure processed cooked rice was suppressed by adding trehalose. In sensory evaluations, high pressure processed cooked rice received lower ratings. However, adding trehalose before processing helped maintain higher ratings compared to processing ordinary rice without trehalose. The present findings provide insights into using high pressure treatment in cooking systems.